Against (Design) Research - Ferdinand Indrajaya (Bina Nusantara University, 2011)
The content of this article is an attempt to show that the word research in traditional sense (within the Cartesian scheme) is hostile to design activity. It will reduce the process of design into a merely fix mechanical process, burying the aspect of imagination, creativity, and more importantly proposing in it that is a crucial aspect to design. This imposition might indiscipline (in a formal academic sense) design as a discipline in human sciences. In order to achieve this, the article is divided in three sections. The first section will discuss what scientific research is and what traditionally presupposed in it: objective, neutral, and a-historical; simply the disinterestedness of research. As for the second, epistemological concerns on traditional scientific research from two philosophers of science will be discussed: Thomas S. Kuhn and Paul K. Feyerabend. As for the third, the closing section, an attempt to delineate design and what designers do in comparison to scientists’ will be discussed. It is how design and designers are different in their manners with traditional science and scientist.